ANALIZA SVODA STOPALA UČENIKA SREDNJE ŠKOLE PROSEČNE STAROSTI OD 15 DO 18 GODINA TEHNIČKE ŠKOLE U TUTINU - Admira Koničanin; Fadilj Eminović; Zoran Bogdanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This paper presents the results of the foot in the population of high school students, averag age of 15 to 18 years of the Technical School in Tutin.The sampleis introduced by population of 420 students of both sexes, 171 boys and 249girls.The aim of the work is to analize incidence of false ceiling toes, and to what extent there is sending down of the foot in high school students.